The gift of the great buffalo - Lindstrom, Carole, 1964- (Bloomsbury Children's Books, Bloomsbury Publishing Inc., 2025)
After days of no buffalo sightings, Rose, a young Métis-Ojibwe girl, defies instructions to stay at camp, dons her father's wolf skin, and successfully tracks a herd of buffalo.